Pendidikan Kewirausahaan Berbasis Historioprenership dalam Persfektip Global di Prodi Ilmu Sejarah Universitas Jambi - Fatonah Fatonah; Denny Defrianti (Proceeding International Conference on Malay Identity, 2022)
Abstract: Entrepreneurship Education of Historioprenership on Global Perspective in History Study Program, Universitas Jambi The purpose of this writing article is to find out the development of a historio-preneurship-based on entrepreneurship curriculum in a global perspective and the impact of implementing a historio-preneurship-based on entrepreneurship curriculum for graduates of the Universitas Jambi history study program. The method used in this research were descriptive qualitative method and library research. Based on Indonesia backgrond thhat have many advantages and gifts from the Creator, especially in large and multicultural human resources and vast natural resources which are rich in various flora, fauna and many islands. So, to respond the digital era of globalization, universities should be required to prepare scholars or graduates who are superior, innovative and competitive nationally and internationally so that university graduates are expected to be immediately ready to compete and produce competent resources. The results of developing a curriculum that adapts to the development of science, technology and the environment so that university graduates have human resources that are competitive in the current era of globalization. One of the curriculum that is widely offered by almost all tertiary institutions in Indonesia is an entrepreneurship-based curriculum, one of which is the historiopreneurship curriculum in the History Study Program at the Universitas Jambi. This is deemed necessary, because higher education is a place to prepare graduates who have an entrepreneurial spirit and are ready to compete in society with various skills in facing the challenges of the globalization era. It can be concluded that in the era of globalization, higher education institutions must participate in preparing good quality education to produce quality generations/graduates who have hard skills and soft skills so that graduates are ready to compete in the era of the industrial revolution 4.0 and the era of society 5.0. In addition, the tertiary curriculum determines the quality of education. One of the curriculu. that is currently widely implemented in tertiary institutions is a curriculum that is oriented towards entrepreneurship , this also applies to the history study program at the Universitas Jambi. The impact of the entrepreneurship and historiopreneurship curriculum is to prepare graduates who are independent, ready to work and create jobs and change the mindset of graduates or change the general public of society. Keywords: Historiopreneurship, Enterpreneurship, History Study Program